A MONOGRAPH OF AGLAIA, sect. LANSIUM Kosterm. (MELIACEAE) - a. j. g. h. kostermans (Reinwardtia, 1966)
The history of the genus and the arguments for merging it with Aglaia,,areexpounded.The section Lansium of Aglaia is characterized by simple hairs and contains 15 species.Aglaia kinabaluensis, A. intricatoreticulata, A. membrartacea and A. chartacea are new to science.New combinations: Aglaia anamallayana, aquea, breviracemosa, dubia, koster- mansii, pedicellata, sepalina. New names: A. steenisii (base: L. pedicellatum Kosterm.), A. pseudolansium (base: L.cinereum Hiern).The genus Reinwardtiodendron Koorders is merged with Aglaia (sect Lansium);new name: A. reinwardtiana (base R. celebicum Kds.).Excluded are: Lansium decandrum Roxb. and L. hum.ile Hassk., which are referred to Aphanamixis (A. decandra and A. humile, comb, nov.).